2021
DOI: 10.3390/su13084095
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Activities and Resources in Archaeological Museums for the Teaching of History in Formal Education

Abstract: The research objectives of this paper are to compare the activities which have been prepared in the design of field trips from the perspective of teachers and museum educators, as well as to describe the use of resources and materials from the point of view of educational agents. The research method is quantitative, based on the study of a descriptive comparative cross-sectional survey. The participants are 442 teachers of early years, primary and secondary education, visiting two archaeological museums with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
3
0
2
Order By: Relevance
“…The other three adopted a qualitative approach: through means of interviews, document analysis or physical observations, specific instructional practices were examined, such as inclusive heritage education practices (Gómez-Hurtado, Cuenca-López & Borghi, 2020), museum educators' questioning practices (Tigert, Fotouhi & Kirschbaum, 2021) or museum educators' more general approach towards instruction (Zarmati, 2020). Theoretically, these studies used a variety of frameworks, both general pedagogical, such as the Vygotskian sociocultural theory of learning (Tigert et al, 2021) as well as more specific ones such as heritage education (Gómez-Hurtado et al, 2020), or a combination through adopting a 'learner-based model of heritage education' (Escribano-Miralles et al, 2021a). Zarmati (2020) introduced the concept of pedagogical content knowledge (PCK) at the beginning of her study.…”
Section: Category 1: Focus On Instructional Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…The other three adopted a qualitative approach: through means of interviews, document analysis or physical observations, specific instructional practices were examined, such as inclusive heritage education practices (Gómez-Hurtado, Cuenca-López & Borghi, 2020), museum educators' questioning practices (Tigert, Fotouhi & Kirschbaum, 2021) or museum educators' more general approach towards instruction (Zarmati, 2020). Theoretically, these studies used a variety of frameworks, both general pedagogical, such as the Vygotskian sociocultural theory of learning (Tigert et al, 2021) as well as more specific ones such as heritage education (Gómez-Hurtado et al, 2020), or a combination through adopting a 'learner-based model of heritage education' (Escribano-Miralles et al, 2021a). Zarmati (2020) introduced the concept of pedagogical content knowledge (PCK) at the beginning of her study.…”
Section: Category 1: Focus On Instructional Practicesmentioning
confidence: 99%
“…Dialogue between the two institutions, if existing, did not seem to enable discussion about for example goals, students' prior knowledge or their learning needs (Wright-Maley et al, 2013). Besides, analysis of self-reported practices revealed that mostly only teachers considered how classroom and museum education could be connected, and only they were engaged in designing pre-and post-visit activities (Escribano-Miralles et al 2021a;Zarmati 2020). These empirical findings contrast with the ideal scenarios of the cases above, but point towards the challenges that accompany the many opportunities that collaborative approaches entail.…”
Section: Category 3 Collaboration Between Schools and Museums Before ...mentioning
confidence: 99%
“…Υπάρχουν αναφορές για μη ορθή παιδαγωγική χρήση των μουσείων και στέρηση ευκαιριών αξιοποίησής τους προς όφελος των μαθητών (Trofanenko & Segall, 2012). Σε ακόμη πιο πρόσφατες εργασίες αναδεικνύεται η ανάγκη για σχεδιασμό μιας πολιτικής η οποία θα προωθεί τη συνεργασία σχολείου-μουσείου ώστε να ενθαρρύνεται η προετοιμασία για την επίσκεψη στο μουσείο από πλευράς σχολείου και εκπαιδευτικών και θα αξιοποιείται η επίσκεψη ως εργαλείο μάθησης στην τάξη (Escribano-Miralles et al, 2021). Σε άλλη πρόσφατη εργασία, αναφέρεται ότι το μουσείο εντοπίζεται χαμηλά στις προτεραιότητες των εκπαιδευτικών για τους μαθητές τους, με πιθανές εξηγήσεις τα ζητήματα πρόσβασης σε αυτό, τη διδακτική υποστήριξη και την παιδαγωγική τεχνογνωσία (Kissel et al, 2019).…”
Section: ερευνητικό ενδιαφέρον και προβληματικήunclassified
“…Η τάση αυτή εμφανίζεται να έρχεται σε κάποια αντίθεση με τα δεδομένα από τη βιβλιογραφική ανασκόπηση που αφορούν στην ελληνική πραγματικότητα και κάνουν λόγο για απροθυμία των εν ενεργεία εκπαιδευτικών να διασυνδέσουν το σχολείο με το μου-Δημητριάδη, Μαλαφάντης σείο, έλλειψη διάθεσης το χρησιμοποιήσουν παιδαγωγικά και έκφραση αισθημάτων άγχους και ανησυχίας κατά την επίσκεψη στο χώρο του μουσείου (Ανδρέου et al, 2007• Δάλκος, 2002• Καλογιάννη, 2015• Σηφάκη, 2017• Στεφάνου κ.ά., 2013). Το ίδιο διαπιστώνεται και σε σχέση με τα δεδομένα από τη διεθνή επιστημονική κοινότητα που παρουσιάστηκαν (Anderson, 1999• Escribano-Miralles et al, 2021• Griffin, 2011• Kisiel, 2005• Kissel et al, 2019• Tal et al, 2005• Talboys, 2016• Trofanenko & Segall, 2012, στα οποία η αξιοποίηση του μουσείου ως παιδαγωγικού εργαλείου φαίνεται να είναι χαμηλά στις προτεραιότητες των εκπαιδευτικών οι οποίοι σε αρκετές περιπτώσεις νιώθουν ανεπαρκείς, χωρίς τις απαραίτητες γνώσεις, εμπειρίες και αυτοπεποίθηση, ενώ οι υποψήφιοι παιδαγωγοί που αποτέλεσαν το δείγμα της έρευνάς μας εμφανίστηκαν ενθουσιώδεις, αποφασιστικοί (μέσος όρος πρόθεσης από 5,90 έως 6,01) και με αυξημένη αυτοπεποίθηση και αυτοέλεγχο (μέσος όρος αντιλαμβανόμενου συμπεριφορικού ελέγχου από 5,11 έως 5,42), όσον αφορά στην παιδαγωγική αξιοποίηση του μουσείου. Τα ευρήματα όμως αυτά θα μπορούσαν να έχουν τις παρακάτω πιθανές εξηγήσεις.…”
Section: συζήτηση και συμπεράσματαunclassified
“…The data and case studies are old and lack any sense of the times, and there is no way to mobilize the interest of induced college students, and the educational effect has little effect. With the rapid development of big data technology in the context of the Internet, the change of knowledge and the transmission of information no longer need to be achieved through someone or some institution [7][8][9].…”
Section: Introductionmentioning
confidence: 99%